Highly sensitive optical biosensor based on silicon-microring-resonator-loaded Mach–Zehnder interferometer. (16th March 2017) - Yoshida, Soichiro; Ishihara, Shintaro; Arakawa, Taro; Kokubun, Yasuo
Abstract: We propose and demonstrate a novel biosensor based on a silicon-single-microring-resonator-loaded Mach–Zehnder interferometer (MRR-MZI), and discuss the design of the sensor theoretically. Owing to the combination of an MZI and the enhanced phase change in a microring resonator (MRR), high sensitivity is expected to be realized. The designed MRR-MZI sensor is fabricated using a CMOS-compatible process, and its sensing characteristics are measured using ethanol solutions with a concentration of less than 3 wt % and avidin solutions. The sensitivity of the MRR-MZI to changes in the environmental refractive index is increased by approximately 50 times compared with that of a simple MRR. In addition, avidin solution with a concentration as low as 20 pM was successfully detected.